Managers’ information literacy: a case study of a Cluster in Brazil - Ottonicar, Selma Leticia Capinzaiki; Valentim, Marta Lígia Pomim; Feres, Glória Georges (AtoZ: novas práticas em informação e conhecimento, 2020)
Introduction: Managers need to be information literate to take effective decisions. Method: This study aims to analyze the situation of information literacy in small business organized as clusters and develop a case study about the electronic industrial cluster in the city of Garça, Sao Paulo State. A literature review supported the elaboration of a theoretical Information literacy; documentary research to characterise the historical research universe; a case study, covering a set of eleven (11) small companies in the electronics sector. Results: The managers value information, knowledge and lifelong learning. However, they do not understand that information literacy influences competitive advantage. The results demonstrate that information literacy is an influential factor in the business competitiveness of these organizations and therefore effectively contributes to the survival of companies in the market. Information literacy contributes directly to small businesses’ growth organized as a cluster. Conclusions: They rely on a group, evaluate information to create innovation through creativity.